Anti-CD166/4-1BB chimeric antigen receptor T cell therapy for the treatment of osteosarcoma - Yitian Wang; Wei Yu; Jian Zhu; Junjie Wang; Kaishun Xia; Chengzhen Liang; Huimin Tao (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background Chimeric antigen receptor (CAR)-engineered T cells have displayed outstanding performance in the treatment of patients with hematological malignancies. However, their efficacy against solid tumors has been largely limited. Methods In this study, human osteosarcoma cell lines were prepared, flow cytometry using antibodies against CD166 was performed on different cell samples. CD166-specific T cells were obtained by viral gene transfer of corresponding DNA plasmids and selectively expanded using IL-2 and IL-15. The ability of CD166.BBζ CAR-T cells to kill CD166+ osteosarcoma cells was evaluated in vitro and in vivo. Results CD166 was selectively expressed on four different human osteosarcoma cell lines, indicating its role as the novel target for CAR-T cell therapy. CD166.BBζ CAR-T cells killed osteosarcoma cell lines in vitro; the cytotoxicity correlated with the level of CD166 expression on the tumor cells. Intravenous injection of CD166.BBζ CAR-T cells into mice resulted in the regression of the tumor with no obvious toxicity. Conclusions Together, the data suggest that CD166.BBζ CAR-T cells may serve as a new therapeutic strategy in the future clinical practice for the treatment of osteosarcoma.